Symbols and meanings in school mathematics - Pimm, David (Routledge, 1995)
This timely book explores the various uses and aspects of symbols in school mathematics and the notion of mathematical meaning. In addition, the author addresses a number of key issues for the 1990s eg.changes within mathematical functioning.